Life histories determine divergent population trends for fishes under climate warming - Hui-Yu Wang (Nature Portfolio, 2020)
The ongoing increase of ocean temperatures could have major effects on fish populations. Here the authors model relationships between sea temperature and life history traits in over 300 species, showing that while warming overall accelerates life history traits, changes in population growth depend on the fast–slow life-history continuum.